2005
DOI: 10.2527/2005.831182x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a condensed tannin-containing forage on methane emission by goats1

Abstract: The objective of this study was to compare methane emission by goats consuming the condensed tannin-containing forage sericea lespedeza (Les-pedeza cuneata) or a mixture of crabgrass (Digitaria ischaemum) and Kentucky 31 tall fescue (Festuca arundinacea). Two groups of 12 Angora does (initial average BW = 41.5 +/- 2.7 kg) that previously grazed a pasture of sericea lespedeza or crabgrass/tall fescue for approximately 4 mo were used. After 1 wk of adaptation to metabolism cages, gas exchange was measured for 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
141
1
16

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(169 citation statements)
references
References 21 publications
11
141
1
16
Order By: Relevance
“…This is in agreement with some previous reports, both tannin phenolics (Carulla et al, 2005;Puchala et al, 2005) and non tannin phenolics (Jayanegara, 2009b). The mechanisms of phenolic compounds in inhibiting methane formation in ruminants have been proposed by Tavendale et al (2005), i.e.…”
Section: Factor Loading and Relationship Between Variablessupporting
confidence: 94%
“…This is in agreement with some previous reports, both tannin phenolics (Carulla et al, 2005;Puchala et al, 2005) and non tannin phenolics (Jayanegara, 2009b). The mechanisms of phenolic compounds in inhibiting methane formation in ruminants have been proposed by Tavendale et al (2005), i.e.…”
Section: Factor Loading and Relationship Between Variablessupporting
confidence: 94%
“…Many plants contain tannins, and these are often tropical shrub legumes. Animal trials with plants or extracts of condensed tannin-containing Lotus corniculatus, Lotus pedunculatus and Acacia mearnsii reduced CH 4 production in small ruminants (sheep, alpaca, goats) by up to 30% without altering digestibility (PinaresPatiñ o et al, 2003c; Carulla et al, 2005;Puchala et al, 2005). More recently, Tiemann et al (2008) reported that the inclusion of the tannin-rich shrub legumes species Callinadra calothyrsus and Fleminga macrophylla in the diet reduced CH 4 emissions in growing lambs by up to 24%, but this was associated with reduced organic matter and fibre digestibility.…”
mentioning
confidence: 99%
“…Reference [34] reported that, roughage based diets might increase the tVFA and decrease the A:P ratio. Both reference [25], and [35] reported that tVFA varies with the response to phenolic compounds in the diet by depressing fibre degradation, with the extent of which depends upon the chemical structure of the phenolic compound and the species of methanogen [36]. Although not observed in this study, reference [7] reported that an increasing pH might decrease tVFA.…”
Section: B In Vitro Rumen Fermentation Characteristicsmentioning
confidence: 54%
“…Reference [25] observed that tannin-containing forage diets have the potential to reduce CH 4 emissions in ruminants. In addition, saponins can improve rumen fermentation and nitrogen metabolism [27].…”
Section: B In Vitro Rumen Fermentation Characteristicsmentioning
confidence: 99%